2016
DOI: 10.1088/0031-9155/61/15/5606
|View full text |Cite
|
Sign up to set email alerts
|

Direct estimation and correction of bias from temporally variable non-stationary noise in a channelized Hotelling model observer

Abstract: Channelized Hotelling model observer (CHO) methods were developed to assess performance of an x-ray angiography system. The analytical methods included correction for known bias error due to finite sampling. Detectability indices ([Formula: see text]) corresponding to disk-shaped objects with diameters in the range 0.5-4 mm were calculated. Application of the CHO for variable detector target dose (DTD) in the range 6-240 nGy frame(-1) resulted in [Formula: see text] estimates which were as much as 2.9×  greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(63 citation statements)
references
References 10 publications
1
62
0
Order By: Relevance
“…Under quantum noise‐limited conditions, the model was found to be linear with changes in quantum x‐ray fluence, linear with changes in test object diameter as predicted by the Rose model, and sensitive to the difference in penumbral blur between small and large focal spots during x‐ray angiography magnification imaging. Next, we found that temporally variable nonstationary noise (detector electronic noise) resulted in positive bias to d′ estimates for low DTD and proposed theory to and methods to correct it . That same 96‐channel, bias‐corrected CHO model was used for this work.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Under quantum noise‐limited conditions, the model was found to be linear with changes in quantum x‐ray fluence, linear with changes in test object diameter as predicted by the Rose model, and sensitive to the difference in penumbral blur between small and large focal spots during x‐ray angiography magnification imaging. Next, we found that temporally variable nonstationary noise (detector electronic noise) resulted in positive bias to d′ estimates for low DTD and proposed theory to and methods to correct it . That same 96‐channel, bias‐corrected CHO model was used for this work.…”
Section: Discussionmentioning
confidence: 97%
“…Model observer theory and experimental methods were similar to those previously described . Analytical methods were executed using MATLAB ® (Mathworks, Natick, MA).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations